A Literature Review on Transgenic Crops in Indonesia and ASEAN Countries: Transgenic Research Development and Future Prospects for Food Sovereignty - Zulkarnain, Alivia; Nurhafitri, Amanda; Tjong, Djong Hon; Idris, Muhammad (Jurnal Biologi Tropis, 2025)
The growing global population, climate change, and limited agricultural land are key challenges threatening food security. One innovative solution is the development of transgenic crops, genetically engineered plants that possess superior traits such as resistance to pests, diseases, abiotic stress, and improved nutritional value. This literature review explores the historical development of transgenic research in Indonesia and other ASEAN countries, the technological approaches used—including Agrobacterium-mediated transformation, biolistic methods, and CRISPR/Cas9 - and the future prospects for achieving national food sovereignty. While countries like China and the Philippines have advanced in Genetically Modified Organism (GMO) commercialization, Indonesia remains in the research phase due to various obstacles, including limited expertise, low research funding, regulatory constraints, and public acceptance. Strengthening regulatory frameworks, human resource development, and international collaborations are essential for supporting sustainable agricultural biotechnology. This paper highlights the need for a strategic, science-based approach to integrating transgenic technology into Indonesia's agricultural system as part of its long-term food security and innovation agenda.